Respuesta :

so let's name the numbers x and y.

we know that their sum, x+y is [tex]7\frac{2}{8} [/tex]

and that that their difference, x-y is [tex]2\frac{4}{8} [/tex]

so, from the last one we can find out x:

x-y=[tex]2\frac{4}{8} [/tex]
x=[tex]2\frac{4}{8} [/tex]+y


we can substitute this into the first one:

[tex]2\frac{4}{8} [/tex]+y+y = [tex]7\frac{2}{8} [/tex]

[tex]2\frac{4}{8} [/tex]+2y = [tex]7\frac{2}{8} [/tex]

2y=[tex]4\frac{6}{8} [/tex] (7-2=5, but you have to "borrow" one because the fraction of the number from which you substract is smaller than of the other number)

so y=[tex]2\frac{3}{8} [/tex]

then x will be
x=[tex]2\frac{4}{8} [/tex]+[tex]2\frac{3}{8} [/tex]
x=[tex]4\frac{7}{8} [/tex]









ACCESS MORE